(untitled) (College of Basic Education Research Journal, 2025)
Current research dealt with biography of venerable Imam Abu Hafs al-Nasafi, one of scholars of fifth Hijri century . One of prominent scholars in Qur’anic readings . This can be concluded through his treatise entitled “ Al-Taysir fi Al-Tafsir “ Research mentions mass transmitted readings of Qur’an , along with practical examples . Research was divided into two sections. First : discussed biography of venerable Imam Abu Hafs al-Nasafi, such as his name, lineage, sheikhs, students, and works. As for second section, researchers discussed his presentation of mass transmitted Qur’anic readings, accompanied by examples, and then conclusion. Lastly but not least , a list of sources and references.